2002
DOI: 10.1016/s0002-9440(10)61110-8
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Morphogenesis and Differentiation after Adoptive Transfer of Human Endothelial Cells to Immunodeficient Mice

Abstract: To establish a model for adoptive transfer of endothelial cells, we transferred human umbilical vein endothelial cells (HUVECs) to immunodeficient mice (Rag

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Other techniques for producing microvessels from cultured ECs that have been described (10,12) use Matrigel, a proangiogenic, incompletely defined tumor matrix with controversial effects on vessel formation (25). Such models are unlikely to be suitable for long-duration functional studies due to apoptosis of the human ECs and ingrowth of murine vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other techniques for producing microvessels from cultured ECs that have been described (10,12) use Matrigel, a proangiogenic, incompletely defined tumor matrix with controversial effects on vessel formation (25). Such models are unlikely to be suitable for long-duration functional studies due to apoptosis of the human ECs and ingrowth of murine vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Such EC-based neovascularization strategies may be enhanced by genetic manipulation of the cells before implantation, e.g., by expressing antiapoptotic proteins or factors that enhance vessel growth and maturation (8,9). Although several techniques of EC implantation (using extracellular matrices of Matrigel or type I collagen) have been described (10)(11)(12), the resulting vessels have not been extensively characterized. We previously reported that implantation of collagen͞fibronectin gels containing human umbilical vein endothelial cells (HUVECs) retrovirally transduced with the antiapoptotic gene Bcl-2 (but not control-transduced ECs) efficiently recruit host SM cells to form chimeric microvessels within the abdominal wall of immunodeficient mice.…”
mentioning
confidence: 99%
“…However, the vascular component of tumors in these experimental models is provided by the murine host, and therefore is not adequate to study the effect of antiangiogenic strategies in human endothelium. 7 Conversely, long-lasting functional human blood vessels can be engineered in nude mice after implantation of human primary endothelial cells (ECs), [8][9][10][11][12][13] but they lack the influence of the tumor component. Coimplantation of tumor cells along with human ECs provides a best-suited model of tumor vasculature, 14 but it is not an accurate surrogate of the complex tumor microenvironment.…”
mentioning
confidence: 99%
“…In the absence of endostatin, human endothelial cells suspended in Matrigel form complex human vessels that make xenogeneic contact with the murine vascular system, carry murine blood, and recruit perivascular ␣-smooth muscle actin-positive cells. 44 However, systemic delivery of yeast-derived, recombinant human endostatin leading to serum levels of 30 to 35 ng/mL during 30 days almost completely …”
mentioning
confidence: 99%
“…44,46 HUVECs or PMECs suspended in liquid Matrigel were subsequently injected subcutaneously, as detailed in previous work. 44 Briefly, endothelial cells (3 ϫ 10 5 ) suspended in 200 L Matrigel were injected in the midline of the abdomen, carefully positioning the needle between the epidermis and the muscle layer. The liquid Matrigel stiffens at body temperature to form a solid plug.…”
mentioning
confidence: 99%